Two new species of Hymenochaetaceae on Dracaena cambodiana from tropical China - Du, Ping (MycoKeys, 2021)
Two new wood-rotting fungi in the family Hymenochaetaceae, Fulvifomes dracaenicolasp. nov. and Hymenochaete dracaenicolasp. nov., are described and illustrated from tropical China based on morphological characteristics and molecular data. It is worth to mention that both of them grow on Dracaena cambodiana which is a kind of angiosperm tree distributed in tropical regions. F. dracaenicola is characterised by perennial, pileate, triquetrous basidioma with yellowish brown fresh pores which becoming honey yellow with silk sheening upon drying, a dimitic hyphal system in trama and monomitic in context, and subglobose basidiospores measuring 4.8–5 × 4–4.1 μm. H. dracaenicola is characterised by annual, resupinate basidioma with a clay buff hymenophore, a dimitic hyphal system, absence of tomentum and cortex, presence of subulate setae, absence of cystidia, presence of cystidioles and simple hyphidia, and oblong ellipsoid basidiospores measuring 5.2–5.8 × 2.5–2.8 µm. The phylogenetic analyses based on ITS + nLSU rDNA sequences confirm the placement of two new species respectively in Fulvifomes and Hymenochaete. Phylogenetically closely related species to the two new species are discussed.